TNF, SOLUBLE RECEPTORS AND AUTOANTIBODIES TO TNF OF PATIENTS WITH RHEUMATOID ARTHRITIS AND HEALTHY DONORS - E. A. Golikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The content of autoantibodies to TNF in the sera of patients with rheumatoid arthritis (RA) in conjunction with the definition of soluble receptors and TNF was investigated. A significant increase in the content of TNF and I and II types soluble receptors to TNF in sera of RA patients in the acute stage and of responding to therapy RA patients compared with relatively healthy donors was demonstrated. In determining autoantibodies subclasses a significant increase in the relative content of subclasses IgG2, IgG3 and IgG4 autoantibodies in sera of RA patients in the acute stage compared with relatively healthy donors, as well as a significant increase in the relative content of subclasses IgG2 and IgG4 autoantibodies in RA patients in the acute stage compared with RA patients, responding to therapy were shown. Thus we have shown the presence of antibodies, soluble receptors to TNF and cytokine in the serum of relatively healthy donors and RA patients, herewith taking into account significant changes in the relative content of the subclasses of autoantibodies and in the content of TNF and soluble receptors we can talk about the functional role of the autoantibodies and soluble receptors to TNF in the pathology.